Niat Brain Brain pada Fresh Graduate: Studi Kasus Tren #KaburAjaDulu di Wilayah Jabodetabek 2025 - Wasi Bagasworo; Davin Prayoga Pahlevi; Eka Putri Ginaristi; Nugroho, Kayla Aryani Putri; Khairun Nisa Tanjung; Tri Mardiani; Gregorius Agung Steven Simanjuntak (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2026)
The increasing popularity of the #KaburAjaDulu trend on social media has intensified concerns regarding the potential brain drain among Generation Z fresh graduates in Indonesia. This phenomenon reflects the growing intention of young talents to seek better career opportunities, higher living standards, and broader self-development prospects abroad. This study aims to examine the influence of push factors and pull factors on brain drain intentions and their subsequent impact on the #KaburAjaDulu phenomenon among fresh graduates in the Greater Jakarta area (Jabodetabek). A quantitative research approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), with data collected through an online survey of 100 Generation Z fresh graduates. The findings reveal that both push factors and pull factors have positive and significant effects on brain drain intentions. Furthermore, brain drain intentions significantly influence support for the #KaburAjaDulu movement. The study also confirms that brain drain acts as a mediating variable in the relationship between push and pull factors and the #KaburAjaDulu phenomenon. These findings highlight the importance of improving employment quality, career development opportunities, employee welfare, and overall quality of life in Indonesia to reduce the tendency of talent migration among young graduates.